Analisis faktor–faktor yang mempengaruhi tingkat kemiskinan di Kabupaten Tebo - Syaputra Simarmata, Rudy; Junaidi, Junaidi; Nurhayani, Nurhayani (Konsentrasi Ekonomi Sumberdaya Alam dan Manusia, Prodi Ekonomi Pembangunan, Fakultas Ekonomi dan Bisnis, Universitas Jambi, 2025)
This study aims to determine and analyze the effect of GRDP, Government Expenditures, Population and Literacy Rates on the Poverty Level in Tebo Regency. This study uses time series data during the years 2005-2019. Data collection techniques were obtained in ready-made form from the Regency Central Statistics Agency (BPS), library studies, literature, documentation and others. The results of this study indicate that based on the F test of the variables of GRDP, Government Expenditure, Literacy Rate, Population to Poverty Level, the value is 5.530 with a 95% confidence level and the t table value is 4.766. Based on the value of the Coefficient of Determination (R²) it can be seen that the R 2 value is 0.375, which means that the variables GRDP, Government Expenditure, Literacy Rate and Population have an influence on the Poverty Level of 0.375 or 37.5% while the remaining 62.5% comes from factors others not examined. From the research results and conclusions, suggestions can be given that is seen from the results of the study although GRDP, Government Expenditures, Literacy Rates and Population have an effect on reducing poverty levels in Tebo Regency. by empowering potential economic sector changes.